ANALISA TENTANG STRATEGI BELAJAR SISWA SD DALAM UPAYA MENGHADAPI UJIAN NASIONAL - Erintasari, Erna (Journal of Professional Elementary Education, 2024)
This study aims 1) to find out learning strategies in facing the national elementary school exams 2) to find out the preparations that elementary school students need to prepare for the national exams. The research method used in this research is descriptive research method with quantitative approach. The sample used in the study were students with a random sampling technique. The data in this study are in the form of a test that aims to determine student learning strategies in an effort to face the national exam. The data analysis method used descriptive analysis and independent sample t-test. The results of this study show that in learning there must be a strategy as an outline of the direction in action to achieve the goals that have been determined. The strategy can also be understood as all the means and power to deal with certain targets under certain conditions in order to obtain the maximum expected results. There are several strategies that are usually used in conducting the national exam learning method as for the strategies as follows: 1) Quantum teaching Learning Strategies 2) Quantum Learning Learning Strategies 3) Inquiry Learning Strategies 4) Problem Based Instruction learning strategies 5) Contextual Teaching and Learning strategies Learning and preparation for the national exam are matters relating to the preparations made by students to face the national exam including 1) Mental preparation, 2) body health, 3) Self-confidence, 4) Self preparation, 5) Preparation technical, 6) Preparation of exam materials